Minor degree of hypohydration adversely influences cognition: a mediator analysis - David Benton (American Journal of Clinical Nutrition, 2016)
Background: The assumption that small changes in hydration statusare readily compensated by homeostatic mechanisms has been littlestudied. In this study, the influence of hypohydration on cognition wasexamined.Objectives: We assessed whether a loss of ,1% of body mass dueto hypohydration adversely influenced cognition, and examined thepossible underlying mechanisms.Design: A total of 101 individuals were subjected to a temperature of308C for 4 h and randomly either did or did not consume 300 mLH2O during that period. Changes in body mass, urine osmolality,body temperature, and thirst were monitored. Episodic memory, focusedattention, mood, and the perceived difficulty of tasks weremeasured on 3 occasions. The data were analyzed with the use ofa regression-based approach whereby we looked for variables that mediatedthe influence of hypohydration on psychological functioning.Results: Drinking water improved memory and focused attention.In the short-term, thirst was associated with poorer memory. Later,a greater loss of body mass was associated with poorer memory andattention (mean loss: 0.72%). At 90 min, an increase in thirst wasassociated with a decline in subjective energy and increased anxietyand depression, effects that were reduced by drinking water. At180 min, subjects found the tests easier if they had consumed water.Conclusions: Drinking water was shown, for the first time to ourknowledge, to benefit cognitive functioning when there was a lossof ,1% body mass at levels that may occur during everydayliving. Establishing the variables that generate optimal fluid consumptionwill help to tailor individual advice, particularly in clinicalsituations.